PENDAMPINGAN PENGGALIAN KEBUTUHAN SISTEM INFORMASI PENGELOLAAN PRODUK DAN JUAL BELI PADA KANTIN SMK SEMEN GRESIK - Anugrah, Indra Gita; Witra, Widyasari Puspa Permata (Jurnal Pengabdian Masyarakat dan Lingkungan, 2024)
Requirement Engineering (RE) is the initial stage in the Software Development Life Cycle (SDLC) which functions to analyze the needs of the organization. However, the RE stage is often carried out without comprehensive knowledge of the information system that is appropriate to the conditions of the organization. Therefore, the community service aims to assist SMK Semen Gresik in meeting the needs of an information system that suits the school's needs. The mentoring process is carried out through several stages, namely needs analysis, interviews with school officials, and direct observation of operational activities. The result of this community service is identifying the need for a specific information system that is able to support school management effectively. It is hoped that these findings can become the basis for developing an integrated information system, so that it can increase the operational efficiency and effectiveness of SMK Semen Gresik. Apart from that, this mentoring activity also provides insight to schools regarding the importance of information systems in supporting the education and management process. In addition, this assistance succeeded in exploring relevant information system needs and became an important first step in implementing technology in the SMK Semen Gresik educational environment.